High-frequency electrical stimulation (HFES) data lean and obese Zucker rat tibialis anterior muscle: Regulation of glycogen synthase kinase 3 beta (GSK3B) associated proteins - Gautam K. Ginjupalli; Kevin M. Rice; Anjaiah Katta; Nandini D.P.K. Manne; Ravikumar Arvapalli; Miaozong Wu; Shinichi Asano; Eric R. Blough (Data in Brief, 2018)
Anaerobic exercise has been advocated as a prescribed treatment for the management of diabetes: however, alterations in exercise-induced signaling remain largely unexplored in the diabetic muscle. Here, we compare the basal and the in situ contraction-induced phosphorylation of the AMPK, GSK3beta, and Shp2 in the lean and obese (fa/fa) Zucker rat tibialis anterior (TA) muscle following a single bout of contractile stimuli. This article represents data associated with prior publications from our lab (Katta et al., 2009; Katta et al., 2009; Tullgren et al., 1991) [1–3] and concurrent Data in Brief articles (Ginjupalli et al., 2017; Rice et al., 2017; Rice et al., 2017; Rice et al., 2017) [4–7]. Keywords: Diabetes, Skeletal muscle, High-frequency electrical stimulation (HFES), Zucker rat, Tibialis anterior, GSK3b